2015
DOI: 10.1016/j.wasman.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of drainage water quality from a landfill cover built with secondary construction materials

Abstract: The aim of this study was to evaluate the drainage water quality from a landfill cover built with secondary construction materials (SCM), fly ash (FA), bottom ash (BA) sewage sludge, compost and its changes over time. Column tests, physical simulation models and a full scale field test were conducted. While the laboratory tests showed a clear trend for all studied constituents towards reduced concentrations over time, the concentrations in the field fluctuated considerably. The primary contaminants in the drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…A camada de cobertura final, objeto deste estudo, é uma medida de proteção ambiental constituída de multicamadas que serve para reduzir a infiltração de água para o lixo depositado e para minimizar emissões de gás do aterro para a atmosfera (TRAVAR et al, 2015), além de reduzir a ocorrência de outros inconvenientes como odores e vetores de doenças. Segundo a NBR 13896/97 a concepção de uma camada de cobertura final de um aterro exige pouca manutenção e deve ser prevista no plano de encerramento do aterro, de forma minimizar a infiltração de água na célula, não estar sujeita a erosão, acomodar assentamento sem fratura e possuir um coeficiente de permeabilidade inferior ao solo natural da área do aterro (ABNT, 1997 …”
Section: No Ano De 2010 O Brasil Aprovou a Política Nacional De Resídunclassified
“…A camada de cobertura final, objeto deste estudo, é uma medida de proteção ambiental constituída de multicamadas que serve para reduzir a infiltração de água para o lixo depositado e para minimizar emissões de gás do aterro para a atmosfera (TRAVAR et al, 2015), além de reduzir a ocorrência de outros inconvenientes como odores e vetores de doenças. Segundo a NBR 13896/97 a concepção de uma camada de cobertura final de um aterro exige pouca manutenção e deve ser prevista no plano de encerramento do aterro, de forma minimizar a infiltração de água na célula, não estar sujeita a erosão, acomodar assentamento sem fratura e possuir um coeficiente de permeabilidade inferior ao solo natural da área do aterro (ABNT, 1997 …”
Section: No Ano De 2010 O Brasil Aprovou a Política Nacional De Resídunclassified
“…Solid waste disposal creates a great problem for land and air degradation if it is dumped openly (Hai and Ali, 2005) so proper landfills are required with proper covering (Travar et al, 2015). FGDs and personal interviews have revealed that due to the increase in population the amount of waste is increasing every day and is creating pressure on dumping site.…”
Section: Land Contaminationmentioning
confidence: 99%
“…Currently, landfill covers are made of either natural materials, which primarily include compacted clay and modified clays with stabilizing additives or synthetic materials, such as geocomposites, polymer composites, and painting materials [10][11][12][13][14]. Natural materials are easily obtainable, affordable, and accompanied by stable engineering performance.…”
Section: Introductionmentioning
confidence: 99%